PROMOTING CHILD-FRIENDLY EDUCATION IN THE DIGITAL AGE: A COMMUNITY SERVICE PERSPECTIVE - Anselmus Sudirman; Eri Setiawan; Evi Septiani (UIN Sunan Kalijaga, 2022)
Child-friendly education is an important program that provides children from various socio-cultural and ethnic backgrounds with safe, comfortable, and nonviolent learning activities at the family, school, and community. This community service-based article aims to describe (1) the fundamental reasons for revitalizing child-friendly education and (2) the critical principles and elements that allow children to develop their potential in the digital age fully. This program used a dialogic approach to deliver the topic under discussion, involving twenty participants, including parents and teenagers, in Mlese, Klaten Regency, Central Java Province, Indonesia. The dialogic interaction takes the form of (1) presenting material related to child-friendly education in the digital age, (2) investigating problems in small groups based solely on subtopics, and (3) openly discussing solutions to such problems. The results of data analysis from this interactive dialogue affirmed that human-to-human oral interactions enable problem-solving. Children can develop essential values of honesty, dignity, respect, and safety when key ideas and components of child-friendly education are incorporated into their school, schools and community-based platforms.